2000
DOI: 10.1111/j.1445-5994.2000.tb00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture outcomes: quality of life and functional status in older adults living in the community

Abstract: The effects of impaired balance and mobility along with reduced functional and social independence are reflected in the diminished QOL perceived by the fracture group. This indicates that many do not return to their pre-fracture lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 19 publications
3
63
0
3
Order By: Relevance
“…To our knowledge, this is the first time that a randomized trial has been set up with OT training as the single intervention. In relation to the often unfavorable long-term effects of a hip fracture demonstrated in previous studies (Hall et al 2000), the relatively simple and restricted contribution by the occupational therapist in our trial thus seems to have paid off in terms of benefit to the patients and their families. Intervention trials concentrating on the effects of the occupational therapist's role in patient care and rehabilitation, if not completely lacking, are certainly difficult to find in the literature.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, this is the first time that a randomized trial has been set up with OT training as the single intervention. In relation to the often unfavorable long-term effects of a hip fracture demonstrated in previous studies (Hall et al 2000), the relatively simple and restricted contribution by the occupational therapist in our trial thus seems to have paid off in terms of benefit to the patients and their families. Intervention trials concentrating on the effects of the occupational therapist's role in patient care and rehabilitation, if not completely lacking, are certainly difficult to find in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown the selfreported HRQL to be impaired 3 and up to 12 months postoperatively (Borgqvist et al 1992, Johansson et al 1998, Hall et al 2000, Randell et al 2000, van Balen et al 2001, Tidermark et al 2002, van Balen et al 2003, Suriyawongpaisal et al 2003. However, in a relatively recent study in the US, Peterson et al (2002) reported that the patient's physical function, bodily pain, social function, vitality, emotional role, mental health and general health seemed to have recovered 6 months after the fracture.…”
mentioning
confidence: 99%
“…Due to their frequency, hip fractures are one of the most challenging public health concerns, often leading to considerable consequences, including disability (2) and premature death (3,4). Ongoing pain and limited physical mobility can severely compromise quality of life (5). Approximately 20% of US Medicare patients die within 6 months of sustaining a hip fracture (6).…”
Section: Introductionmentioning
confidence: 99%
“…7 Approximately 20% of Medicare patients in the United States die within 6 months of sustaining a hip fracture. 8 Bisphosphonates are a class of drugs known to interfere with osteoclast bone resorption, a fact that has been exploited clinically for the treatment and prevention of osteoporosis for several decades. In oncology, bisphosphonates have traditionally been used in the palliative care of patients with bone metastases.…”
Section: Introductionmentioning
confidence: 99%